Creative mending : beautiful darning, patching and stitching techniques - Noguchi, Hikaru (Tuttle, 2022)
"Mend, rethink, transform, recreate! Mending your favorite fabric items--from jeans to sweaters to sofa covers--becomes a true art form in Stylish Mending. In this book, mending guru Hikaru Noguchi shows you her entire range of valuable techniques--from embroidery and patching to darning and felting--that are just challenging enough for experienced menders. Noguchi's basic rules of mending are that the repair should suit the fabric and its user, and that there are lots of creative ways to create beautifully customized repairs-some subtle, others making a statement. She provides 13 techniques that show you how to: Apply creative repairs to both knitted and woven fabrics ; Use yarn, floss, ribbon, and fabric to reinvent well-loved garments ; Make understated repairs that add just a touch of contrast, color, or texture ; Use visible mending techniques for bold repairs ; Darn with felt to add body and dimension to a repaired item ; Match your repairs to the damage, the fabric, and the wearer ; Maneuver through tricky places like inseams and underarms ; And more! The 13 illustrated lessons and over 300 color photos in this book provide detailed examples for all the basic techniques. Lots of variations plus plenty of tips and examples (67 in all) provide you with all the guidance you need to rethink and repair beautifully. The stunning photos will inspire you to get creative on that fraying neckline or worn elbow!"--